A multinuclear (1H, 13C, 31P and 195Pt) magnetic resonance spectroscopy study of mixed ligand platinum(II) complexes with new N,N-dialkyl-N'-acyl(aroyl)thioureas as ligands - Mtongana, Sibusiso (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2002.